A Survey on Multilingual Text Conversion and Speech Generation Workflow - Athri K Hegde,; Bhoomika B K,; Dheeraj T N,; Karthik N G,; Dr. Laxmi V, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Human communication is based on language, which enables cross-cultural sharing of concepts, feelings, and information. By enabling people to comprehend and communicate in various languages, multilingualism improves communication. However, because of the variety of languages, scripts, and linguistic systems, there are still major obstacles to smooth multilingual communication. In order to overcome these obstacles, technologies like text summarization, machine translation, optical character recognition (OCR), and text-to-speech (TTS) have become essential. Accuracy problems with different scripts and handwriting styles still exist even if OCR enables text extraction from digital or physical materials. Despite the tremendous advancements in translation systems, issues with context preservation and low-resource languages still exist. Summarization approaches often fail to maintain coherence in multilingual environments, despite their intended reduction of information overload. TTS systems provide accessibility, especially for visually impaired users, but they must account for linguistic nuances and differences in pronunciation between languages. This study examines the state-of-the-art techniques, models, and frameworks developed to overcome these linguistic and technological barriers in the field of multilingual text processing, while also emphasizing important research contributions for more intelligent and inclusive systems.
Keywords: Multilingual; OCR; Summarization; Translation; TTS